International remittances and productivity in sub-Saharan Africa - Simplice Asongu; Joseph Nnanna (African Governance and Development Institute (AGDI), 2024)
his research investigates how enhancing remittances affects total factor productivity (TFP) dynamics in Sub-Saharan Africa. The Generalised Method of Moments (GMM) empirical strategy is adopted for the purpose of the study and the engaged TFP dynamics are: TFP, real TFP, welfare TFP and real welfare TFP. Significant net effects are not apparent from enhancing remittances for TFP, real TFP growth and welfare TFP while positive net effects are apparent on real welfare TFP. The unexpected findings are elucidated and policy implications are discussed. This study has complemented the attendant literature by assessing how growing remittances influence dynamics of TFP in Sub-Saharan Africa.
Keywords: E23; F24; F30; O16; O55; 330; Economic Output; Remitances; Sub-Saharan Africa